Parametric optimization of near-equatorial twin-spacecrafts trajectory based on ground-track performance measure requirements. - Djojodihardjo, Harijono; A.Gunter, A. Aq'Grabin (2012)
Parametric optimization study is carried out on Performance Measure for assessing the benefits of relevant ground-track parameters and Instantaneous Overlap Area (IOA) in near earth and near-equatorial twin-satellite formation flying to explore its potential for of spacecraft formation flying as space platform to carry out Tropical Resources and Environment Monitoring mission. The present study also emphasizes two aspects: the dynamics of relative motion of multiple spacecrafts and the desirable ground tracks beneficial for tropical environmental and resources monitoring missions. Relative motion dynamics incorporating Clohessy-Wiltshire Equation for circular orbits is used as a reference. Related to the relevance of Ground-Track based characteristics and to optimize computational efforts, the performance metric is synthesized as a off between exact definition and intuitive judgment.